The neurobiology of transition to psychosis: clearing the cache - Palaniyappan, Lena (J Psychiatry Neurosci, 2017)
The prepsychotic phase of schizophrenia is not only important for indicated prevention strategies, but also crucial for developing mechanistic models of the emergence of frank psychosis (transition). This commentary highlights the work of Dukart and colleagues, published in this issue of the Journal of Psychiatry and Neurosicence, who sought to identify MRI-based anatomic endophenotypes of psychosis in a well-characterized sample of patients with at-risk mental state (ARMS) and first-episode psychosis (FEP). Conceptual and translational challenges in clarifying the neurobiology of transitional prepsychotic states are discussed. A role of intracortical myelin in the neurobiology of transition is proposed. Transition may not be an outcome of “progressive structural deficits”; it may occur due to inadequate compensatory responses in the predisposed. The need to revise our current “deficit-oriented” models of neurobiology of psychosis in the wake of burgeoning evidence indicating a dynamic process of cortical reorganization is emphasized.